Study of the Performance, Architecture, and Design of Current Reference in Integrated Circuit - Dr. Dharamjit,; Dr. K. B. Singh, (International Journal of Scientific Research in Science and Technology, 2024)
Another fundamental building block for integrated circuits is the current reference. Transistors in integrated circuits must have stable bias currents in order to have stable transconductances. This biasing is usually done by an on-chip current reference, which derives a stable bias current from a voltage reference (such as the one discussed in the previous chapter). The availability of stable bias currents is especially important for a fully implantable recording system, where reliable bias currents must be available to keep the analog amplifiers in the proper mode of operation. The current levels provided must be low to keep down the overall power consumption. This paper discusses the design and performance of the current reference in integrated circuits.
Keywords: FIRS; Electrical Component; MUX; Noise